Risiko Produksi Dan Faktor Yang Mempengaruhi Produksi Usahatani Padi Sawah Tadah Hujan (Studi Kasus Di Desa Tompobulu, Kecamatan Tompobulu, Kabupaten Maros) - Irawati Irawati; Arifin Arifin; Mohammad Anwar Sadat (Jurnal Agribis, 2021)
This reseacrgh was conducted in Tompobulu Village, Tompobulu District, Maros Regency. The formulation of the problem in this study is twofold, namely how much is the risk of rainfed lowland rice farming production factors affect the production of raindfed lowland rice farming in tompobulu village, tompobulu district, Maros Regency and to determine tthe factors that affect the production of rainfed lowland rice farming in Tompobulu. this study uses quantitative data to explain phenomena that are clear and there are already large instruments. There two date used, namely primary data collected from rice farming families who have been selected as reseacrh samples in the village. Then the data includes the amount of rice production. Secondary data, namely data obtained from primary data its elf as a saource that can be seen that rainfed rice farming TompobuluVillage, Tompobulu District, Maros Regency, based on the coefficient of variation (KV) is categorized as risky with a KV value of 0,59 (KV>50). The factor that influence the production of rainded rice farming in tompobulu Village, Tompobulu District, Maros rgency are land area and amount of fertizer.